ANALYSIS OF SIMULATION EFFECT OF INCREASED TAX AND REGIONAL GOVERNMENT SPENDING ON CONSUMPTION OF LAMPUNG PROVINCE COMMUNITIES - Wangke, Freddy; Hidayat, Herlin; Petronila, Thio Anastasia (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
The purpose of this study is to analyze the effect of increased local government taxes and expenditure on the consumption of Lampung Province society. The estimation model in the simultaneous model of the increase in taxes and expenditure of the Lampung provincial government uses the 2 SLS (Two-Stage Least Squares) method. The simulation results of a tax increase of 10% reduced the Gross Regional Domestic Product of Lampung Province by 0.03% and the consumption of Lampung Province by 0.03%. This is also shown by the decrease in demand for the Province's money by 0.01%. On the other hand, the simulation results of the Lampung Province Government spending increase by 10% raised the Lampung Province Regional Domestic Products by 2.06% and the Lampung Province people's consumption by 0.04%. In conclusion, the increase in regional government expenditure is a driving factor that provides stimulus in addition to the Gross Regional Domestic Product and the consumption of the Lampung Province community, as well as to the activities of private investors and regional exports and imports including the money supply.